AQP4 as a vintage autoantigen: what do we know till now? (2022)
ABSTRACT: Autoimmune diseases are characterized by the presence of autoantibodies against autoantigens that induce inflammatory responses that damage tissues and organs, leading to leading to irreversible disturbances. Autoimmune responses attack a specific organ, or tissue in an early phase and after becoming multisystemic. Some autoimmune diseases are related to previous exposure to pathogens. Molecular mimicry between antigens from pathogens and humans is considered a key factor involved in triggering the autoimmune response. This could lead to the development of systemic autoinflammatory disorders that enhance damage, releasing new antigens that continue to exacerbate and activate the disease. In this immune response, autoantibodies and T-cell receptors play pivotal roles that increase the loss of tolerance to self-antigens and promote tissue injury and damage to organs. In neuromyelitis optica, the human antigen AQP4 is attacked by autoantibodies that alter water channels in astrocytes and other cells, resulting in neuropathological diseases. This phenomenon has been characterized in autoimmune diseases such as multiple sclerosis and systemic lupus erythematosus. However, what do we know about its genesis or pathophysiology? This review updates these issues and explores the phenomenon’s origin. (Tomado de la introducción)